(untitled) (Advances in Military Technology, 2018)
The article is focused on the development of the underwater ballistic model of a supercavitating projectile fired from an underwater firearm. The supercavitating flows and their influences on the ballistic characteristics of the projectile are studied. The presented mathematical model is validated and experimentally verified for the supercavitating projectile of 5.7 mm in diameter fired from a smooth bore underwater rifle.